Pengaruh Audit Tenure Dan Reputasi Kap Terhadap Kualitas Audit Pada Perusahaan Indeks L45 Di Bursa Efek Indonesia Tahun 2015-2019 - Aznedra .; Rizki Eka Putra (Universitas Riau Kepulauan, 2020)
This study aims to analyze and provide empirical evidence of the influence of audit tenure, reputation of audit firm. Audit quality is measured by earnings surprise benchmark. This approach was adopted by Rossieta and Wibowo from one of Carey and Simnett audit quality analysis models. Hypothesis (1) Audit tenure positively affect to the audit quality, (2) reputation of audit firm positively affect to the audit quality, (3) Firm Size negative affect to the audit quality, (3) Audit tenure and reputation of audit firm have posittively effect to audit quality. The research used 100 sample of manufacturing companies listed on Bursa Efek Indonesia (BEI) from 2015 – 2019. Determination of the sample using purposive sampling method. Data from this study were obtained from financial statements of manufacturing firms drawn from the Indonesia Stock Exchange and Indonesian Capital Market Directory. To analyze the effect of independent variable on the dependent variable, data were analyzed by logistic regression analysis. The result shows that audit tenure have positive and significant effect to the audit quality and reputation of audit firm have negatife and have not significant effect to the audit quality